1982
DOI: 10.1016/0016-2361(82)90223-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized-bed gasification of some Western Canadian coals

Abstract: Three different Western Canadian coals were gasified with air and steam in a fluidized bed of 0.73 mm Ottawa sand and coal, at atmospheric pressure, and temperatures of 1023-1175 K to produce a low Btu gas. The coals •:, tested were of two types: one non-caking and two caking coals. The results were compared with those previously obtained for the same three coals when gasified in essentially the same equipment, but operated as a spouted bed. The effects of temperature, coal feed rate, air to coal ratio, steam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Australian coal was gasified at atmospheric pressure in an internally circulating fluidized bed with a draft tube by Kim et al The effects of reaction temperature, oxygen/coal mass ratio, coal feed rate, and steam/coal mass ratio on composition of product gas, carbon conversion, cold gas efficiency and gas yield, and calorific value were determined. Similar work was done also by Kikuchi et al, Gutierrez and Watkinson, and Crnomarkovic et al And more, Cousins et al investigated the reactivity of chars formed in fluidized bed gasifiers and found the char reactivity declines rapidly during its formation as part of the pyrolysis of the coal. The effect of pyrolysis time on char reactivity in a fluidized bed was discussed by Liu et al, and they found that a longer pyrolysis time led to lower reactivity of a char, while this effect leveled off as pyrolysis time increased.…”
Section: Introductionsupporting
confidence: 55%
“…Australian coal was gasified at atmospheric pressure in an internally circulating fluidized bed with a draft tube by Kim et al The effects of reaction temperature, oxygen/coal mass ratio, coal feed rate, and steam/coal mass ratio on composition of product gas, carbon conversion, cold gas efficiency and gas yield, and calorific value were determined. Similar work was done also by Kikuchi et al, Gutierrez and Watkinson, and Crnomarkovic et al And more, Cousins et al investigated the reactivity of chars formed in fluidized bed gasifiers and found the char reactivity declines rapidly during its formation as part of the pyrolysis of the coal. The effect of pyrolysis time on char reactivity in a fluidized bed was discussed by Liu et al, and they found that a longer pyrolysis time led to lower reactivity of a char, while this effect leveled off as pyrolysis time increased.…”
Section: Introductionsupporting
confidence: 55%
“…The fluidized bed appears better for Roselyn coal, no significant differences are evident for Forestburg or Sukunka coal, and with the Balmer rejects where weak gases were produced the spouted bed appeared marginally better. There is no strong evidence of the capability of the spouted bed to be operated at lower air/coal ratios as was previously reported from smaller scale tests (Gutierrez and Watkinson 1982).…”
Section: (2)mentioning
confidence: 54%
“…Some preliminary comparisons were made in a 0.15-m dia. unit (Gutierrez and Watkinson 1982). It appeared that at similar operating conditions the gas quality from the fluidized bed was better than from the spouted bed.…”
mentioning
confidence: 98%
“…A large number of studies have been performed to investigate the fluidized bed coal gasification (see for example Gutierrez and Watkinson, Ocampo et al, and Ju et al). However, a detailed experimental investigation and analysis of the fluidized bed gasification with a focus on the high ash coals is not found in the open literature.…”
Section: Introductionmentioning
confidence: 99%